Transport behavior difference and transport model of long- and short-chain per- and polyfluoroalkyl substances in underground environmental media: A review. (15th June 2023) - Li, Hui; Dong, Qianling; Zhang, Meng; Gong, Tiantian; Zan, Rixia; Wang, Wenbing
Abstract: Perfluoroalkyl carboxylic acids (PFCAs) and perfluoroalkyl sulfonates (PFSAs), which are the most commonly regulated and most widely concerned per- and polyfluoroalkyl substances (PFAS) have received increasing attention on a global scale due to their amphiphilicity, stability, and long-range transport. Thus, understanding the typical PFAS transport behavior and using models to predict the evolution of PFAS contamination plumes is important for evaluating the potential risks. In this study, the effects of organic matter (OM), minerals, water saturation, and solution chemistry on the transport and retention of PFAS were investigated, and the interaction mechanism between long-chain/short-chain PFAS and the surrounding environment was analyzed. The results revealed that high content of OM/minerals, low saturation, low pH, and divalent cation had a great retardation effect on long-chain PFAS transport. The retention caused by hydrophobic interaction was the prominent mechanism for long-chain PFAS, whereas, the retention caused by electrostatic interaction was more relevant for short-chain PFAS. Additional adsorption at the air-water and nonaqueous-phase liquids (NAPL)-water interface was another potential interaction for retarding PFAS transport in the unsaturated media, which preferred to retard long-chain PFAS. Furthermore, the developing models for describing PFAS transport were investigated and summarized in detail, including the convection-dispersion equation, two-site model (TSM), continuous-distribution multi-rate model, modified-TSM, multi-process mass-transfer (MPMT) model, MPMT-1D model, MPMT-3D model, tempered one-sided stable density transport model, and a comprehensive compartment model. The research revealed PFAS transport mechanisms and provided the model tools, which supported the theoretical basis for the practical prediction of the evolution of PFAS contamination plumes. Graphical abstract: Image 1 Highlights: High-organic matter/mineral, low saturation/pH, divalent cation more control long-chain PFAS. Retardation effect on long-chain PFAS was more significant than short-chain PFAS. Hydrophobic interaction was the prominent mechanism for affecting long-chain PFAS. Electrostatic interaction was more relevant for affecting short-chain PFAS. Nine types of transport models can be used to simulate PFAS transport.